Pengaruh Pemberian Ekstrak Kulit Buah Manggis (Garcinia mangostana L.) Menghambat Flexi Cranial Embrio Ayam Umur 48 Jam - Anggraeni, Yessy Mulyanur; Rahardjo, Bambang; Rahayu, Indriati Dwi (-)
Embryonic development forms three layers of germinativum that is endoderm, mesoderm and ectoderm. At the beginning of intrauterine fetus exchange of substances through diffusion, but in line with the development of the embryo, nutrition is not obtained through diffusion alone. Endoderm lining mesoderm cells will then be formed angioblasts as an early sign of vascularity. In the development of flexi cranial can be known from the development of the brain and heart which is characterized by bending the head of the embryo and decreased heart from the cranial down. The development of a normal vascular system will have an effect on organogenesis and morphogesis processes. If there are disturbances in the process of growth and development at that stage can cause congenital abnormalities. Xanthones mangosteen peel is rich in benefits, but in research on the effects of xanthones on embryos is still very limited and has not been able to explain their effects on the condition of the fetus. The study was conducted with the aim to determine the effect of mangosteen peel extract inhibiting the flexi cranial of 48 hours chicken embryos using doses of 100 µg/mL, 150 µg/mL and 200 µg/mL. Mangosteen peel extract is injected into chicken eggs less than 7 days after oviposition then incubated for 48 hours. The results showed that mangosteen peel extract inhibited flexi cranial of chicken embryos with Chi-Square test results (p = 0.002). The conclusion of the study was that exposure to mangosteen peel extract inhibited flexi cranial and gave significant results.